2018 7th IEEE International Conference on Biomedical Robotics and Biomechatronics (Biorob) 2018
DOI: 10.1109/biorob.2018.8488083
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Proprioception in Acute and Subacute Stroke: A Robotic Protocol for Highly Impaired Patients

Abstract: Proprioception is a critical component of sensorimotor functions which directly affect recovery after neurological injuries. However, clinical tests of proprioception still lack sensitivity and reliability, while robotic devices can provide quantitative, accurate, and repeatable metrics. This work presents the analysis of the efficacy of a robotic assessment of wrist proprioception in terms of the capability to discern between movements along the different DoFs in a healthy population with a broad range of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the e cacy of both active and passive proprioceptive training in neurologically intact participants and have shown improved proprioceptive thresholds and/or accuracy (19,20,49). Other studies have examined proprioceptive training in stroke survivors and have demonstrated positive outcomes for improvements in proprioceptive function of the upper limb and/or wrist (23,50,51). Notably, these previous studies in stroke have typically relied on passive movement of the limb coupled with verbal report about the status of the limb (i.e., psychometric tasks) or matched behavior with the less-affected limb.…”
Section: Targeted Training Approach For Improving Proprioceptionmentioning
confidence: 99%
“…Previous studies have demonstrated the e cacy of both active and passive proprioceptive training in neurologically intact participants and have shown improved proprioceptive thresholds and/or accuracy (19,20,49). Other studies have examined proprioceptive training in stroke survivors and have demonstrated positive outcomes for improvements in proprioceptive function of the upper limb and/or wrist (23,50,51). Notably, these previous studies in stroke have typically relied on passive movement of the limb coupled with verbal report about the status of the limb (i.e., psychometric tasks) or matched behavior with the less-affected limb.…”
Section: Targeted Training Approach For Improving Proprioceptionmentioning
confidence: 99%
“…The methods proposed so far focus on the proximal joint of the upper limb [31,32], consist of tasks that target only a specific impairment modality (e.g. proprioception, without the possibility to concurrently assess motor function) [33][34][35][36], or fail to provide a detailed evaluation of clinimetric properties of their outcome measures (reliability, measurement error, validity) [11,37]. Reporting of test-retest reliability and measurement error is essential to understand the sensitivity of an assessment metric to capture different impairments and detect changes over time [37], while the study of concurrent validity is important to relate a new technological approach to the commonly accepted assessment methods [38].…”
Section: Introductionmentioning
confidence: 99%